2017
DOI: 10.1038/aps.2016.168
|View full text |Cite|
|
Sign up to set email alerts
|

Geniposide ameliorates TNBS-induced experimental colitis in rats via reducing inflammatory cytokine release and restoring impaired intestinal barrier function

Abstract: Geniposide is an iridoid glycosides purified from the fruit of Gardenia jasminoides Ellis, which is known to have antiinflammatory, antioxidative and anti-tumor activities. The present study aimed to investigate the effects of geniposide on experimental rat colitis and to reveal the related mechanisms. Experimental rat colitis was induced by rectal administration of a TNBS solution. The rats were treated with geniposide (25, 50 mg·kg, ig) or with sulfasalazine (SASP, 100 mg·kg, ig) as positive control for 14 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 45 publications
2
38
0
Order By: Relevance
“…A recent report demonstrates that geniposide ameliorates 2,4,6-trinitrobenzene sulfonic acid-induced experimental rat colitis by reducing inflammation and modulating the disrupted epithelial barrier function via activating the AMP-activated protein kinase signalling pathway (Xu et al. 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report demonstrates that geniposide ameliorates 2,4,6-trinitrobenzene sulfonic acid-induced experimental rat colitis by reducing inflammation and modulating the disrupted epithelial barrier function via activating the AMP-activated protein kinase signalling pathway (Xu et al. 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Geniposide acid contained in 'Tochu-cha' is known to improve hypertension and hyperlipidemia. 6,7) Previous studies showed that geniposide, which is an iridoid glycosides purified from the fruit of Gardenia jasminoides ELLIS, suppressed inflammatory cytokine (TNF-α and IL-1β) release and neutrophil infiltration (myeloperoxidase activity) in the colitis model. 8) Additionally, Eucommia ulmoides OLIV.…”
mentioning
confidence: 99%
“…e amount of geniposide was as follows: GE: 0.154 g/mL. Geniposide has been shown to reduce inflammatory cytokines in intestinal diseases [31]. In this study, we suggest that geniposide may reduce inflammation in reflux esophagitis.…”
Section: Resultsmentioning
confidence: 83%